2016
DOI: 10.18632/oncotarget.9077
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cytokine differentiation and loss of plasticity after SOCS1 inactivation in a cutaneous T-cell lymphoma

Abstract: We propose that deregulated T-helper-cell (Th) signaling underlies evolving Th17 cytokine expression seen during progression of cutaneous T-cell lymphoma (CTCL). Accordingly, we developed a lymphoma progression model comprising cell lines established at indolent (MAC-1) and aggressive (MAC-2A) CTCL stages. We discovered activating JAK3 (V722I) mutations present at indolent disease, reinforced in aggressive disease by novel compound heterozygous SOCS1 (G78R/D105N) JAK-binding domain inactivating mutations. Thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…They belong to the TH17 gene signature [ 90 ], supporting the indicated character of ALCL. Breast implant-associated (BIA)-ALCL, CTLC and ALCL are closely related malignancies and consistently express several aspects of ILC3/TH17 cells aberrantly [ 28 , 69 , 91 ]. In CTCL, IL17F expression is driven via the IL2-JAK3-STAT5 pathway reportedly activated by a particular mutation of SOCS1 [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They belong to the TH17 gene signature [ 90 ], supporting the indicated character of ALCL. Breast implant-associated (BIA)-ALCL, CTLC and ALCL are closely related malignancies and consistently express several aspects of ILC3/TH17 cells aberrantly [ 28 , 69 , 91 ]. In CTCL, IL17F expression is driven via the IL2-JAK3-STAT5 pathway reportedly activated by a particular mutation of SOCS1 [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast implant-associated (BIA)-ALCL, CTLC and ALCL are closely related malignancies and consistently express several aspects of ILC3/TH17 cells aberrantly [ 28 , 69 , 91 ]. In CTCL, IL17F expression is driven via the IL2-JAK3-STAT5 pathway reportedly activated by a particular mutation of SOCS1 [ 69 ]. However, our data revealed absence of SOCS1 mutations in ALCL cell lines, excluding this mode of IL17F activation in ALCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of IL-17A has, accordingly, been associated with neutrophilic infiltration into CTCL lesions; whether it is also the case for IL-17F remains to be investigated [70]. Malignant T cells derived from some patients have the capacity to express IL-17A and/or IL-17F via a Jak3/Stat3/Stat5-dependent mechanism but do not express the Th17-linage transcription factor, RORc, or display a characteristic Th17-phenotype [62, 71, 76, 129]. Therefore, expression of IL-17A and IL-17F by the malignant T cells is probably not reflective of Th17 origin, or acquisition of a full-fledged Th17 phenotype, but rather a consequence of dysregulated signaling.…”
Section: The Malignant T Cells Foster Pro-tumorigenic Inflammation Thmentioning
confidence: 99%
“…Since CTCL is a rare disease, and since established criteria for staging and response evaluation for CTCL are limited, few prospective clinical trials for advanced CTCL have been reported, and guidelines for the treatment of CTCL have yet to be established (2, 3). Instead, several preclinical studies have been used to determine the optimal therapy for CTCL (46). Among them, Shono et al reported that mycosis fungoides (MF), the most common subtype of CTCL, shows high expression of CCR4 on the cell surface, correlating with poor prognosis of MF (4).…”
Section: Introductionmentioning
confidence: 99%